APPLICATION OF GREEN SUPPLY CHAIN MANAGEMENT PRACTICES ASSOCIATED WITH TOTAL QUALITY MANAGEMENT AND JUST-IN-TIME FUNCTIONS TO IMPROVE ORGANIZATIONAL PERFORMANCE IN MANUFACTURING COMPANIES - Ahmad Irfangi; Najmudin (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Several prior studies have highlighted the importance of green supply chain management practices in enhancing organization performance but empirical evidences of its operational antecedents are limited. Therefore, the present study aims to evaluate the potential operating antecedents of green supply chain management practices. The present study is unique as it is intended to assess the combined effect of TQM and JIT on green supply chain management practices consequently enhancing organizational performance. For this purpose the data from 318 employees was collected from Indonesian manufacturing companies. The data was analysed using SmartPLS 3 software adopting PLS-SEM approach. The findings of the study reveled a positive relationship of JIT and TQM with green supply chain management practices. The findings also provide empirical evidence of the mediting effect of green supply chain management practices between the relationship of JIT, TQM and organizational performance.